The Story of Us: Constructing Creative Partnerships Through Collaboration. (January 2020) - Southern, Stephen
Drawing constructs and techniques from object relations, schema therapy, and narrative therapy, this article explored means for constructing successful partnerships in collaboration and mentoring. Selected psychodynamics account for the phases and stages in creative collaboration. The initially hierarchal relationship of mentoring is instigative for reparenting and co-constructing of new perspectives. Self-development and service to the community occur within the context of the bridge between you and me . Case studies of mutuality and collaboration were presented to emphasize key constructs and helpful practices. Recommendations were offered to fuel the creative process of collaboration.